Early warning signs of salt marsh drowning indicated by widespread vulnerability from declining belowground plant biomass - Kyle D. Runion; Merryl Alber; Deepak R. Mishra; Mark A. Lever; Christine M. Hladik; Jessica L. O’Connell (Proceedings of the National Academy of Sciences, 2025)
Salt marshes provide valuable ecosystem services but are vulnerable to drowning with accelerated sea-level rise (SLR). Marsh belowground biomass (BGB) production helps avoid drowning by building marsh surface elevation. Reductions in BGB can serve as an early warning sign of marsh deterioration, as they often precede decreases in aboveground biomass (AGB). However, landscape-scale BGB assessments to predict broad trends in marsh deterioration have not been previously available. We applied the Belowground Ecosystem Resiliency Model (BERM) to assess standing stocks and trends in both BGB and AGB over the past decade (2014–2023) across US Georgia coast Spartina alterniflora marshes (691 km 2 ). Over this time period, BGB and AGB averaged 841 ± 323 and 221 ± 14 g m −2 , respectively, but showed opposite trends. BGB decreased on average by 0.94% per year and over most of the marsh area (72%), while AGB increased on average by 0.66% per year and showed a net increase across most of the marsh area (88%). This disconnect suggests that AGB is not a good indicator of marsh resilience, and we highlight two areas with similar AGB but different BGB. Inundation intensity, an important predictor of BGB, rose through time and was negatively related to BGB. SLR trends suggest continuing increases in inundation, which will result in further declines in BGB followed by widespread marsh drowning. Landscape BGB assessments are a valuable tool to identify ecosystem vulnerability and proactively manage salt marshes and the services they provide under rising sea levels.